2003
DOI: 10.1016/s0927-7757(03)00266-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sol–gel-derived nano-particles separated from oil sands fine tailings

Abstract: Methodology has been developed to separate nano-particles of amorphous material from Syncrude fine tailings. Both, separated finer solids and residual coarser solids, were characterized by elemental analysis, X-ray powder diffraction, XPS, SEM, infrared spectroscopy, solid-state NMR, density, and surface area measurements. Based on the results of infrared and X-ray diffraction, the amorphous minerals identified in finer solids included allophanes, halloysite, ferrihydrite, and amorphous silica. The finer fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Similar observations were reported elsewhere. 33 As mentioned earlier, the amount of these organic materials was also measured and confirmed by CHN and TGA analysis. It is worth noting here that the peaks of silica at about 1000 cm −1 , observed after the oxy-cracking reaction, are sharper.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar observations were reported elsewhere. 33 As mentioned earlier, the amount of these organic materials was also measured and confirmed by CHN and TGA analysis. It is worth noting here that the peaks of silica at about 1000 cm −1 , observed after the oxy-cracking reaction, are sharper.…”
Section: Resultsmentioning
confidence: 66%
“…It was reported that these amorphous materials contain allophanes, halloysite, ferrihydrite, and amorphous silica which interact with the inorganic minerals in these solids. 33,42 4. CONCLUSIONS A novel application of the oxy-cracking process was successfully applied for the enhanced settling of solid particles and dewatering of oil sands tailings water.…”
Section: Industrial and Engineering Chemistry Researchmentioning
confidence: 99%
“…A type III isotherm was obtained for all samples suggesting a very weak adsorption interaction of which the fundamentals are not very well understood [32]. The data indicate the presence of both micropores and mesopores in these samples.…”
Section: Textural Propertiesmentioning
confidence: 85%
“…Isopropyl alcohol decreases the interaction of water with the pore wall during drying. This prevents agglomeration of clay particles resulting in higher surface area product [23].…”
Section: Methodsmentioning
confidence: 99%